2013
DOI: 10.1128/jb.00121-13
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcal Rgg-Like Regulator ElrR Activates Expression of the elrA Operon

Abstract: The Enterococcus faecalis leucine-rich protein ElrA promotes virulence by stimulating bacterial persistence in macrophages and production of the interleukin-6 (IL-6) cytokine. The ElrA protein is encoded within an operon that is poorly expressed under laboratory conditions but induced in vivo. In this study, we identify ef2687 (renamed elrR), which encodes a member of the Rgg (regulator gene for glucosyltransferase) family of putative regulatory proteins. Using quantitative reverse transcription-PCR, translati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 79 publications
2
19
0
2
Order By: Relevance
“…first defined the role of Rgg in S. gordonii as a regulator gene of glucosyltransferases (Sulavik et al ., ; Sulavik & Clewell, ). Rgg‐like regulators (sometimes called MutR) have since been found in a wide range of Gram‐positive bacteria (Sanders et al ., ; Chaussee et al ., ; Qi et al ., ; Samen et al ., ; Ibrahim et al ., ; Chang et al ., ; Dumoulin et al ., ) and control a variety of bacterial processes, including production of the cysteine proteinase SpeB in S. pyogenes (Lyon et al ., ; Chaussee et al ., ), S. mutans lantibiotic bacteriocin production (Qi et al ., ), and virulence gene regulation in S. agalactiae (Samen et al ., ), among others. Only in recent years were Rgg members, once considered to be ‘stand‐alone regulators’ (Kreikmeier et al ., ), shown to respond to SHPs that serve as pheromones.…”
Section: Rgg Regulators and Short Hydrophobic Peptides (Shps)mentioning
confidence: 99%
“…first defined the role of Rgg in S. gordonii as a regulator gene of glucosyltransferases (Sulavik et al ., ; Sulavik & Clewell, ). Rgg‐like regulators (sometimes called MutR) have since been found in a wide range of Gram‐positive bacteria (Sanders et al ., ; Chaussee et al ., ; Qi et al ., ; Samen et al ., ; Ibrahim et al ., ; Chang et al ., ; Dumoulin et al ., ) and control a variety of bacterial processes, including production of the cysteine proteinase SpeB in S. pyogenes (Lyon et al ., ; Chaussee et al ., ), S. mutans lantibiotic bacteriocin production (Qi et al ., ), and virulence gene regulation in S. agalactiae (Samen et al ., ), among others. Only in recent years were Rgg members, once considered to be ‘stand‐alone regulators’ (Kreikmeier et al ., ), shown to respond to SHPs that serve as pheromones.…”
Section: Rgg Regulators and Short Hydrophobic Peptides (Shps)mentioning
confidence: 99%
“…ElrA is encoded by the elr operon , which encodes two other WxL surface proteins, a small LPXTG-motif protein and a putative transmembrane protein proposed to form cell surface complexes [ 1 4 ]. Expression of the elr operon is under the control of the positive regulator elrR [ 4 , 5 ]. The elrA gene is poorly expressed in vitro , but it can be induced by complex biological milieu such as serum or urine, which suggests the tightly regulated control of elrA expression in response to in vivo signals [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Expression of the elr operon is under the control of the positive regulator elrR [ 4 , 5 ]. The elrA gene is poorly expressed in vitro , but it can be induced by complex biological milieu such as serum or urine, which suggests the tightly regulated control of elrA expression in response to in vivo signals [ 5 , 6 ]. Previously, we showed that inactivation of the elrA gene resulted in significantly reduced virulence in a mouse model of peritonitis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ou seja, uma proteína formada apenas por alfa-hélices, como predito para a família de RT Rgg (RRNPP). 71,98 Com essa informação, foram selecionadas estruturas de reguladores transcricionais (homólogos estruturais) com apenas alfa-hélices e que possuíam a estrutura terciária predita para a família RRNPP, para utilizar como modelo de busca no método de substituição molecular. Ao todo, três estruturas foram obtidas provenientes de três diferentes tipos de cristais de ElrR6HIS, em grupos espaciais distintos.…”
Section: Determinação Das Fases Cristalográficas De Elrr6hisunclassified
“…106 Como apenas um sítio de DNA foi determinado, para ligação deste RT, 71 sua unidade biologicamente ativa mais provável deve ser o dímero.…”
Section: Elrrunclassified